2019
DOI: 10.3390/ijerph16214148
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between Air Pollution and Neonatal Deaths: A Case of Asian Countries

Abstract: The rapid economic growth in Asian countries has witnessed a persistent increase in air pollution complementing adverse health challenges for children in these countries. Quantification of health effects attributable to air pollution (PM2.5) is important in policy implications to tackle air pollution and associated health problems. This study aims to explore the nexus between air pollution and neonates’ deaths embedded in acute respiratory infection. We collected panel data from the 12 most vulnerable Asian co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
(68 reference statements)
1
18
0
Order By: Relevance
“…Similarly, Næss et al [ 21 ] identified that the air pollutant indicators (NO 2 , PM 10 , and PM 2.5 ) had a significant effect on all causes of death for both men and women in Oslo, Norway. Similar findings were also identified in the works of Anwar et al [ 18 ] for 12 of the most vulnerable Asian countries, Shan et al [ 23 ] for China, Lehtomäki et al [ 20 ] for Nordic countries, Rajak and Chattopadhyay [ 22 ] for India, and Brito [ 39 ] for Portugal. Clancy et al [ 40 ] maintained that control of the particulate air pollution significantly reduces the death rate from the comparison of pre and post 72 months ban on coal sales in Dublin, Ireland.…”
Section: Literature Reviewsupporting
confidence: 85%
See 1 more Smart Citation
“…Similarly, Næss et al [ 21 ] identified that the air pollutant indicators (NO 2 , PM 10 , and PM 2.5 ) had a significant effect on all causes of death for both men and women in Oslo, Norway. Similar findings were also identified in the works of Anwar et al [ 18 ] for 12 of the most vulnerable Asian countries, Shan et al [ 23 ] for China, Lehtomäki et al [ 20 ] for Nordic countries, Rajak and Chattopadhyay [ 22 ] for India, and Brito [ 39 ] for Portugal. Clancy et al [ 40 ] maintained that control of the particulate air pollution significantly reduces the death rate from the comparison of pre and post 72 months ban on coal sales in Dublin, Ireland.…”
Section: Literature Reviewsupporting
confidence: 85%
“…Similar statistics were also been obtained by Alemu [ 8 ] in the case of 33 African countries from 1994 to 2013. However, Farahani et al [ 25 ] and Anwar et al [ 18 ] found no statistically significant impact of education on infant and neonatal mortality for the global panel and the 12 most vulnerable Asian countries, respectively. By critically analysing the research, it has been observed that past studies did not consider the significance of education in determining the death rate in the panel of most industrialised countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our results are corroborated by the studies of [ 5 , 15 , 16 ], who highlighted a significant relationship between air pollution (PM 2.5 ) and child mortality. The studies in India, China [ 20 , 27 ], and other developing countries [ 3 , 13 , 28 ] have also established a significant relationship between air pollution and health outcomes. Some studies found that the incidence rates of child morbidity and mortality are higher among children living in highly polluted areas [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most hazardous of these sources are human activities, such as nitrogen dioxide from vehicles, sulfur dioxide from power plants, and ground-level ozone, as well as particulate matter. The last type is important due to its ability to penetrate into peoples’ lungs and enter their bloodstream [ 3 , 4 ]. Epidemiological researchers have substantiated that these health impacts are induced by continuing ambient PM 2.5 concentrations and the coherent risk factors that vary from country to country [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation